Science Fiction and Digital Technologies in Argentine and Brazilian Culture - King, E. author. aut Link
IX, 242 p.
Keywords: Fictional narratives produced in Latin America often borrow tropes from contemporary science fiction to examine the shifts in the nature of power in neoliberal society. King examines how this leads towards a market-governed control society and also explores new models of agency beyond that of the individual.